Environmental Water and Sediment Microbial Communities Shape Intestine Microbiota for Host Health: The Central Dogma in an Anthropogenic Aquaculture Ecosystem - Huang, Zhijian; Hou, Dongwei; Zhou, Renjun; Zeng, Shenzheng; Xing, Chengguang; Wei, Dongdong; Deng, Xisha; Yu, Lingfei; Wang, Hao; Deng, Zhixuan; Weng, Shaoping; Ning, Daliang; et al. (Frontiers in Microbiology, 2021)
The increasing evidence has emerged a tight link among environment, intestinal microbiota, and host health status, moreover, the microbial interaction in different habitats is crucial for ecosystems. However, how environmental microbial community assembly governs the intestinal microbiota and microbial communities of multiple habitats contribute to the metacommunity remains elusive. Here we designed two delicate experiments from temporal and spatial scales in a shrimp cultural pond ecosystem (SCPE). Of the SCPE metacommunity, the microbial diversity was mainly contributed by the diversity ofβIntraHabitats and βInterHabitats, and environmental water and sediment microbial communities had a large contribution to the shrimp intestine community with a variety of personalized advanced ecological analyses. Also, microbial assembly of three habitats in the SCPE appeared to be largely driven by stochastic processes. These results enrich our understanding of the “Environment-Intestinal Microbiota-Host Health” closely link relationship, making it possible to be the central dogma for anthropogenic aquaculture ecosystem. Our findings enhance the mechanistic understanding of microbial assembly in the SCPE for further analyzing metacommunities, which has important implications for microbial ecology and animal health.